1999
DOI: 10.1049/el:19990782
|View full text |Cite
|
Sign up to set email alerts
|

Optimised design of fibre-based pulse compressor for gain-switched DFB laser pulses at 1.5 [micro sign]m

Abstract: An optical-fibre based pulse compressor for gain-switched DFB laser pulses has been optimised using a systematic procedure based on the initial complete characterisation of the laser pulses, followed by numerical simulations of the pulse propagation in different types of fibre to determine the required lengths for optimum compression.Using both linear and nonlinear compression techniques, an optimum compression factor of 12 is achieved.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The (linewidth × time) products (FWHM) of the pulses generated had values between 0.32 and 0.44. Since then, DFB gain-switched lasers have become a popular means of generating single-frequency low-chirp pulses of 25 to 30 ps duration [133][134][135].…”
Section: Optical Spectra Of Gain-switched Pulsesmentioning
confidence: 99%
“…The (linewidth × time) products (FWHM) of the pulses generated had values between 0.32 and 0.44. Since then, DFB gain-switched lasers have become a popular means of generating single-frequency low-chirp pulses of 25 to 30 ps duration [133][134][135].…”
Section: Optical Spectra Of Gain-switched Pulsesmentioning
confidence: 99%
“…However, it is clearly advantageous to be able to optimize the pulses generated at the transmitter before employing them in the overall system. In addition, if the complete intensity and phase of the data signal at the transmitter is known, then the system designers will be able to accurately model the transmission of these data signals through the fiber networks [8] and also determine the exact level of dispersion compensation and management that the system will require. In this letter, we have shown that by using the FROG measurement technique, we can retrieve the complete intensity and phase of optical pulses generated using a CW laser diode followed by an external modulator.…”
Section: Discussionmentioning
confidence: 99%
“…5 To predict optical pulse profiles properly in time and frequency domains at each pulse compression stage, it is essential to know the parameters of the gain-switched pulse, such as pulse shape, pulse width, and, most of all, the frequency chirp information of the pulse for optimum pulse compression. 6 The gain-switched pulse is broadly regarded as having linear frequency chirp only, but the actual gain-switched pulse has almost linear chirp around the center of the optical pulse and nonlinear frequency chirp in the vicinity of leading or trailing edges. The presence of nonlinear frequency chirp cannot be overcome due to the variations of carrier density in the gain medium during the pulse buildup time.…”
Section: Introductionmentioning
confidence: 99%